Fatigue methodology for life predictions for the wheel-rail contact area in large offshore turret bearings - T. Lassen; Z. Mikulski (Fracture and Structural Integrity)
The present report presents a fatigue life prediction method for large roller bearings applied in the turret turn table for large loading buoy units. The contact points between wheel and rail in these bearings are subjected to a multi-axial fluctuating stress situation and both surface wear and fatigue cracking may occur. A methodology based on the Dang Van fatigue criterion is adopted. The criterion is based on an equivalent stress defined as a combination of the fluctuation of the shear stress from its mean value at a critical plane and the associated hydrostatic stress at the given time. The present work is supporting the theoretical model by extensive laboratory testing. Both full scale testing of wheel on rail and small scale testing for characterizing the steel material are carried out. An experimental program was carried out with the high strength stainless steel S165M. The Dang Van stress concept is applied in combination with the Random Fatigue Limit Method (RFLM) for life data analyses. This approach gives the opportunity to include both finite lives and the run-outs in a rational manner without any presumption of the existence of a fatigue limit in advance of the data. This gives a non-linear S-N curve for a log-log scale in the very high cycle regime close to the fatigue limit. It is demonstrated how the scatter in fatigue limit decreases when the Dang Van stress concept is applied and that the fatigue limit is occurring beyond 107 cycles